2020
DOI: 10.3389/fphar.2020.01212
|View full text |Cite
|
Sign up to set email alerts
|

Bufei Yishen Formula Restores Th17/Treg Balance and Attenuates Chronic Obstructive Pulmonary Disease via Activation of the Adenosine 2a Receptor

Abstract: the Th17/Treg balance via activating A2aR, which may provide evidence for the clinical application of BYF in the treatment of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…In COPD rats, BYF significantly inhibited the expression of IL-1 β , IL-6, TNF- α , and sTNFR2 induced by cigarette smoke and bacterial infection exposures. The inhibition of BYF on inflammatory response in rat COPD model may be through restoring the Th17/Treg balance by activating adenosine 2a receptor [ 16 ] and modulating the activities of STAT3 and STAT5 [ 17 ]. Th17/Treg imbalance is considered to be important of COPD development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In COPD rats, BYF significantly inhibited the expression of IL-1 β , IL-6, TNF- α , and sTNFR2 induced by cigarette smoke and bacterial infection exposures. The inhibition of BYF on inflammatory response in rat COPD model may be through restoring the Th17/Treg balance by activating adenosine 2a receptor [ 16 ] and modulating the activities of STAT3 and STAT5 [ 17 ]. Th17/Treg imbalance is considered to be important of COPD development.…”
Section: Resultsmentioning
confidence: 99%
“…e inhibition of BYF on inflammatory response in rat COPD model may be through restoring the 17/Treg balance by activating adenosine 2a receptor [16] and modulating the activities of STAT3 and STAT5 [17]. 17/Treg imbalance is considered to be important of COPD development.…”
Section: Screening Of Antioxidant Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is a heterogeneous syndrome associated with an abnormal inflammatory immune response in the lung, 25 characterized by persistent respiratory symptoms and continuous airflow restriction. Studies have confirmed that changes in immune cells play an important role in COPD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies revealed that Chinese medicine (CM) could be applied to treat COPD by regulating various signaling pathways such as JAK2/STAT3, PI3K/Akt/NF-kappaB and EGFR-PI3K-AKT signal pathways, et, al. [ 12 – 18 ].…”
Section: Introductionmentioning
confidence: 99%